Takeover bids - Should the board or shareholders decide? - Ambaras Khan, Mushera Bibi (Chartered Secretaries Canada, 2010)
There is a complex set of factors that typically affect decision-making by the board. These include concerns about employees, the environment and society. That same complexity enters the board's decisions when considering a takeover.